A study on causal relationship between telecommunication consumption and economic variables in Malaysia / Siti Surayah Aziz - Aziz, Siti Surayah (2007)
The purpose of this study is to investigate the causal relationship between telecommunication consumption and macroeconomic variables in Malaysian market. This investigation leads to the determination of the cause and effect of both variables. It determines which variable is affecting the other variable or both variables are affecting each other or both variables are not affecting each other. This research used total telecommunication consumption and macroeconomic variables as the variables. The total consumption of telecommunication is represented by the net income of the major companies that involved in telecommunication sector in Malaysia which are Telekom Malaysia Berhad, Maxis and DiGi.com. While for the macroeconomic variables, it consisted of the Gross Domestic Product (GDP), interest rate, inflation rate and income per capita. The study covered for a period from 1995 until 2005. The data collected is in yearly basis. By using Granger causality method, the result suggested that there is only a unidirectional causality from telecommunication consumption to GDP. Besides that, it is concluded that there is a unidirectional causality from telecommunication consumptions to income per capita. In addition, the study found that there is a unidirectional causality relationship from inflation to telecommunication consumptions. Lastly, this study implies that there is an existing of a bidirectional causality relationship between telecommunication consumption and interest rate in the study.